No one sees God : the dark night of atheists and believers - Novak, Michael (New York : Doubleday, 2008)
Examines the questions and challenges of faith and the conflict between doubt and faith experienced by both atheists and believers, arguing that spirituality effectively answers the questions about life's meaning and purpose.
Introduction : The Darkling plain -- False Starts. Not the way to invite a conversation: Dawkins, Dennett, and Harris -- Nor is this the way: Hitchens -- The Common Darkness. Letter to an Atheist friend -- Heather's spirited reply -- Who Are We, Under These Stars? Horizons, Blicks, and Ockham's razor -- Nothing is by design: everything is by chance -- Thinking about God -- Existence and the existent -- The New Conversation. Secular, but not "secularist" -- The end of the secularist age -- Appendix one. Reflections in Westminster Abbey: up from nihilism -- Appendix two. Favorite "dark" biblical passages.
Includes bibliographical references (p. [293]-300) and index.
Keywords: Christianity and atheism; Apologetics